Research on the Relationship Between High-Commitment Work Systems and Employees’ Unethical Pro-organizational Behavior: The Moderating Role of Balanced Reciprocity Beliefs - Zhang, Min; Zhao, Lijing; Chen, Zhihong (Frontiers in Psychology, 2021)
Based on the social exchange theory, this paper explores the indirect impact of high-commitment work systems on employees’ unethical pro-organizational behavior. Through the analysis of multisource data from 139 companies (including 139 human resource managers and 966 employees), a multilevel structuring equation model is used to verify the study’s hypotheses. The research results show the following findings: (1) High-commitment work systems are significantly positively related to employees’ unethical pro-organizational behavior. (2) High-commitment work systems have indirect effects on the employees’ unethical pro-organizational behavior through the relational psychological contract. The relational psychological contract plays a mediating role in this process. (3) Employees’ balanced reciprocity beliefs significantly enhance the positive effect of relational psychological contracts on employees’ unethical pro-organizational behavior. It can also positively moderate the mediating effect of high-commitment work systems that affect employees’ unethical pro-organizational behavior via relational psychological contract.